Green Hydrogen Production and Combustion in a Solar-Enhanced Brayton-Rankine Cycle: A Case Study in Bandar Abbas, Iran - AmirMahdi Ijadi; Abolfazl Fattahi (Journal of Renewable Energy and Environment)
A study on a real steam power plant in Iran is conducted to explore a novel approach to sustainable hydrogen production by integrating a combined Brayton-Rankine cycle with concentrated photovoltaics. Through the efficient utilization of concentrated sunlight, the system provides the electricity demand of the proton exchange membrane (PEM) electrolyzer, while the input thermal energy required for hydrogen production is supplied by the Rankine cycle. Furthermore, the hydrogen produced is burned in the combustion chamber of the Brayton cycle. The analysis of the first and second laws of thermodynamics is performed. The effects of changes in various parameters, such as the combustion temperature, compressor pressure ratio, boiler outlet temperature, and condenser pressure, on performance are evaluated. The results indicate that energy and exergy efficiency increase with higher outlet steam boiler or combustion chamber temperatures. However, an increase in condenser pressure decreases both efficiencies, despite increasing the net power of the total cycle. Enhancing the current electrical density of the PEM improves hydrogen production by a factor of four, while it elevates the PEM efficiency by only about 9%. The efficiency of the total and Brayton cycles increases by approximately 43% and 50%, respectively, with an increase in the inlet gas turbine temperature from 1200 to 1600K. The exergy efficiency reaches 66% and 57%, respectively, for the Rankine and total cycles, with an increase in boiler temperature from around 600 to 1200K.